1976
DOI: 10.1172/jci108587
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between epicardial ST-segment elevation and myocardial ischemic damage after experimental coronary artery occlusion in dogs.

Abstract: A B S T R A C T The relationship between early and late epicardial electrocardiographic changes as well as those in regional myocardial blood flow (MBF) and the severity of myocardial damage was determined in 12 anesthetized dogs with left anterior descending coronary artery ligation. Radioactive microspheres (15 ,um) were used to measure regional MBF at 15 min (early) and 24h (late) after coronary occlusion. Severity of myocardial damage was assessed by the extent of myocardial creatine phosphokinase depletio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…For group 1 segments resting function was depressed significantly below control levels between 1 to 3 h post-LAD occlusion. Significant increases in NET occurred at each infusion rate (7,14, and 27 pLg/min) at 1, 2, 4, and 6 h postocclusion, and at 7 and 27 jig/min at 8 h. No significant increases occurred at 24 h postocclusion. For group 2, resting function was significantly depressed below control levels at each time period after occlusion (NET = 33±4 at 5 min postocclusion).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…For group 1 segments resting function was depressed significantly below control levels between 1 to 3 h post-LAD occlusion. Significant increases in NET occurred at each infusion rate (7,14, and 27 pLg/min) at 1, 2, 4, and 6 h postocclusion, and at 7 and 27 jig/min at 8 h. No significant increases occurred at 24 h postocclusion. For group 2, resting function was significantly depressed below control levels at each time period after occlusion (NET = 33±4 at 5 min postocclusion).…”
Section: Resultsmentioning
confidence: 86%
“…Histochemical (9), metabolic (10), electrocardiographic (11)(12)(13)(14), rheological (15,16), enzymatic (6), scintigraphic (17), and histologic (18) studies of jeopardized zones of myocardium have been carried out in experimental animals. However, the relationship between these parameters of ischemic injury and the segmental contractile properties of ventricular myocardium is unresolved.…”
mentioning
confidence: 99%
“…The degree of ischemic injury produced during brief coronary artery occlusion is reflected by changes in the magnitude of ST-segment elevation as well as the overall duration. Several investigators have demonstrated that ST-segment elevation measured early after coronary artery occlusion correlates with reductions in myocardial blood flow (Heng et al 1976;Irvin and Cobb 1977;Kjekshus et al 1972;Wégria et al 1949) and cellular damage as estimated by myocardial creatine phosphokinase activity (Heng et al 1976;Maroko et al 1971). It is now postulated that ST-segment changes are caused by intracellular electrical potential differences between normal and ischemic myocytes during different phases of the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…" 12 as well as by data from Cohen and Kirk 13 and Heng et al 14 Holland applied the solid angle theory to the electrical events resulting from transmembrane potential alterations within the ischemic tissue and suggested that factors other than the extent of the ischemic region (e.g., geometry of the ischemic zone, degree of alteration of action potential morphology, changes in intra-and extracellular conductivity) are influential in determining the extent, polarity, and magnitude of the resulting TQ-ST deflection.…”
mentioning
confidence: 75%